Safety and tolerability of transition from inhaled treprostinil to oral selexipag in pulmonary arterial hypertension: Results from the TRANSIT-1 study - Frost, Adaani; Janmohamed, Munir; Fritz, Jason S.; McConnell, John W.; Poch, David; Fortin, Terry Ann; Miller, Chad E.; Chin, Kelly M.; Fisher, Micah; Eggert, Michael; McEvoy, Colleen; Benza, Raymond L.; et al. (The Journal of heart and lung transplantation, 2019)
A long-term trial showed that the oral prostacyclin (PGl2) receptor (IP) agonist, selexipag, delayed disease progression in patients with pulmonary arterial hypertension (PAH). Transition to selexipag in patients treated with more burdensome inhaled therapies that target the prostacyclin pathway may be considered by patients and physicians. The Phase 3b, prospective, open-label TRANSIT-1 (Tolerability and Safety of the Transition From Inhaled Treprostinil to Oral Selexipag in Patients With Pulmonary Arterial Hypertension) study evaluated the safety and tolerability of transition from inhaled treprostinil to oral selexipag. Patients receiving non-prostanoid oral PAH therapy and inhaled treprostinil at stable doses, in World Health Organization Functional Class II/III, with 6-minute walk distance ≥ 300 meters were enrolled. The 16-week main treatment period included downtitration of inhaled treprostinil over 8 weeks and parallel uptitration of selexipag over 12 weeks. Sustained treatment transition at Week 16 was defined as (1) receiving selexipag at Week 16; (2) no selexipag interruption(s) totaling ≥ 8 days; and (3) no inhaled treprostinil or other prostanoids after Week 8. Clinical parameters and patient-reported treatment satisfaction outcomes were assessed at Week 16. All 34 enrolled patients completed the study. At Week 16, 32 patients (94.1%) had stopped inhaled treprostinil and were receiving selexipag. Twenty-eight patients (82.4%) met all criteria for sustained treatment transition. During the study, 3 patients discontinued selexipag due to adverse events. Overall, most adverse events were typical of prostanoid therapies and started during the uptitration phase. In general, patients remained clinically stable throughout treatment and reported improved convenience. Transition to oral selexipag from inhaled treprostinil in PAH patients was successful and well tolerated in most patients, and associated with greater convenience. NCT02471183